Targeted screening of multiple anti-inflammatory components from Chrysanthemi indici Flos by ligand fishing with affinity UF-LC/MS - Huang, Chuanqi; Xiong, Xin; Zhang, Dan; Ruan, Qingfeng; Jiang, Jie; Wang, Fuqian; Chen, Guilin; Cheng, Lu (Frontiers in Pharmacology, 2024)
Chrysanthemi indici Flos (CIF) has been commonly consumed for the treatment of inflammation and related skin diseases. However, the potential bioactive components responsible for its antiinflammatory and sensitive skin (SS) improvement activities, and the correlated mechanisms of action still remain unknown. In this work, it was firstly found that the CIF extract (CIFE) displayed arrestive free radical scavenging activity on DPPH and ABTS radicals, with no significant difference with positive control Trolox (p > 0.05). Then, compared to the negative group, CIFE markedly decreased the productions of the pro-inflammatory cytokines (IL-1β, IL-6, PEG2, TNF-α, IFN-γ, NO) in LPS induced RAW264.7 cells in a dose-dependent manner (p < 0.01). Besides, CIFE strongly inhibited the COX-2 and hyaluronidase (HAase) with the IC50 values of 1.06 ± 0.01 µg/mL and 12.22 ± 0.39 µg/mL, indicating higher inhibitory effect than positive control of aspirin of 6.33 ± 0.05 µg/mL (p < 0.01), and comparable inhibitory effect with indometacin of 0.60 ± 0.03 µg/mL, and ascorbic acid of 11.03 ± 0.41 µg/mL (p > 0.05), respectively. Furthermore, kinetic assays with Lineweaver-Burk plot (Michaelis Menten equation) suggested that CIFE reversibly inhibited the COX-2 and HAase, with a mixed characteristics of competitive and non-competitive inhibition. Thereafter, multi-target affinity ultrafiltration liquid chromatography-mass spectrometry (UF-LC/MS) method was employed to fast fish out the potential COX-2 and HAase in CIFE. Herein, 13 components showed various affinity binding degrees to the COX-2 and HAase, while those components with relative binding affinity (RBA) value higher than 3.0, such as linarin and chlorogenic acid isomers, were deemed to be the most bioactive components for the anti-inflammatory and SS improvement activities of CIFE. Finally, the interaction mechanism, including binding energy, inhibition constant, docking sites, and the key amino acids involved in hydrogen bonds between the potential ligands and COX-2/HAase were simulated and confirmed with the molecule docking analysis. In summary, this study showcased the prominent anti-inflammatory and SS improvement activities of CIF, which would provide further insights on this functional medicinal plant to be a natural anti-SS remedy.